2001
DOI: 10.2527/2001.7961509x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary L-carnitine on growth performance and body composition in nursery and growing-finishing pigs.

Abstract: Two experiments were conducted to determine the effect of dietary L-carnitine on growth performance and carcass composition of nursery and growing-finishing pigs. In Exp. 1,216 weanling pigs (initially 4.9 kg and 19 to 23 d of age) were used in a 35-d growth trial. Pigs were blocked by weight in a randomized complete block design (six pigs per pen and six pens per treatment). Four barrows and four gilts were used to determine initial carcass composition. L-Carnitine replaced ground corn in the control diets to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 12 publications
2
44
1
1
Order By: Relevance
“…These authors concluded that the inability of added fat to elicit a growth response was not altered by supplemented L-carnitine. Previous studies (Owen et al , 2001bSmith et al 1994) had observed reductions in backfat thickness and(or) increased percentage lean of pigs with additions of 50 to 125 ppm of added L-carnitine, contrary to our findings. Since initial carnitine status was not determined in the present study it is unknown if this contributed to the contrasting carcass results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These authors concluded that the inability of added fat to elicit a growth response was not altered by supplemented L-carnitine. Previous studies (Owen et al , 2001bSmith et al 1994) had observed reductions in backfat thickness and(or) increased percentage lean of pigs with additions of 50 to 125 ppm of added L-carnitine, contrary to our findings. Since initial carnitine status was not determined in the present study it is unknown if this contributed to the contrasting carcass results.…”
Section: Discussioncontrasting
confidence: 99%
“…Delany et al (1999) observed an increase in serum insulin with 1% supplemented CLA. The lack of growth response to supplemental L-carnitine agrees with the earlier data of Owen et al (1994Owen et al ( , 2001b and Smith et al (1994). These authors concluded that the inability of added fat to elicit a growth response was not altered by supplemented L-carnitine.…”
Section: Discussionsupporting
confidence: 86%
“…This effect is due to an enhanced rate of β-oxidation of long-chain fatty acids. On the other hand, Owen et al (2001aOwen et al ( , 2001b failed to detect an effect of supplementing 50 or 125 ppm L-carnitine on growth performance of growing pigs. In other studies it was shown that pigs fed a diet supplemented with 50 ppm L-carnitine had a higher daily gain, better feed conversion, better carcass meatiness and thinner backfat (Rekiel and Zackiewicz 2004).…”
Section: Discussionmentioning
confidence: 88%
“…In piglets and growing pigs, L-carnitine supplementation led to a reduction in body fat and an increase in body protein (Heo et al 2000, Owen et al 2001a, 2001b. This effect is due to an enhanced rate of β-oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation